SOCIAL MEDIA STRATEGY THE SALATIGA REGIONAL POLICE FOR SUPPORTING IMAGE TOLERANT CITY IN SALATIGA CITY - Shobron, Yazid; Arenggoasih, Wuri (Universitas Katolik Soegijapranata, 2025)
Social media as a platform for interaction and information sharing has profoundly changed the path people communicate and interact. It has had a significant impact in facilitating global connections, the exchange of ideas, and public participation in public dialogue. In the context of security and order in a city of tolerance, social media strategy becomes an important instrument for the police in building effective communication with the community. This study aims to analyse the social media strategy implemented by the Salatiga Police in maintaining security and order in Salatiga City as a city of tolerance. Using a descriptive approach and case study method, this research explores how social media planning and implementation are conducted by the Salatiga Police. The results show that the social media strategy implemented includes six main aspects, namely (1) determining communication objectives, (2) identifying target audiences, (3) selecting media platforms, (4) determining messages and delivery methods, (5) allocating budgets, and (6) implementation and monitoring. The findings provide insights for police institutions and policymakers in optimising social media as a strategic communication tool to increase public interaction and participation in maintaining security and order in the city of tolerance.